A case study of the impact of regional knowledge services and management on regional economic development - Ran, Na (Daluang: Journal of Library and Information Science, 2023)
Background. Knowledge can give an important contribution to local economic development, but the correlation between library activities and local economic development has not been clarified yet. The purpose of this investigation is to discuss the correlations between library output measures and regional economic measures. Methodology. The raw data obtained via the website of the National Bureau of Statistics of China have been analyzed by correlation coefficient calculations and multivariate regressions. Results and discussion. It was found that there are significant positive correlations between the data of the regional public libraries such as the collections of public libraries owned per person, the total number of circulation of public libraries, the Number of Seats of Reading Room in Public Libraries, the Floor Space of Buildings of Public Libraries Owned per 10000 Population, the Number of Lectures in Public Libraries and the data of their economic development. Linear relationships between library activities and the gross regional product of the five provinces in China and one of China’s direct-controlled municipalities were observed after multivariate regressions were performed on the data. Conclusions. It can be concluded that economic development can benefit the development of libraries, and better education or a more educated population has resulted in more library use. The correlation analysis and multivariate regression analysis can be developed as a new way to measure the societal value of public libraries orientated for economic development or other targets.